2009
DOI: 10.1176/appi.ajp.2008.08081201
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Caudate and Nucleus Accumbens Response to Rewards in Unmedicated Individuals With Major Depressive Disorder

Abstract: Objective Major depressive disorder (MDD) is characterized by impaired reward processing, possibly due to dysfunction in the basal ganglia. However, few neuroimaging studies of depression have distinguished between anticipatory and consummatory phases of reward processing. Using functional magnetic resonance imaging (fMRI) and a task that dissociates anticipatory and consummatory phases of reward processing, the authors tested the hypothesis that MDD participants would show reduced reward-related responses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

70
869
18
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,065 publications
(959 citation statements)
references
References 52 publications
70
869
18
2
Order By: Relevance
“…Symptoms of depression including anhedonia implicate a hypo-responsive reward system in the pathophysiology of depression (Pizzagalli et al, 2005(Pizzagalli et al, , 2009Treadway and Zald, 2011). A wealth of data from both animal studies and human neuroimaging links reward processing to a brain network centered upon the ventral striatum (VS), but also including midbrain, ventromedial prefrontal cortex, posterior cingulate cortex, anterior cingulate cortex, anterior insula, and thalamus (Knutson et al, 2001;Satterthwaite et al, 2007;Kable and Glimcher, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of depression including anhedonia implicate a hypo-responsive reward system in the pathophysiology of depression (Pizzagalli et al, 2005(Pizzagalli et al, , 2009Treadway and Zald, 2011). A wealth of data from both animal studies and human neuroimaging links reward processing to a brain network centered upon the ventral striatum (VS), but also including midbrain, ventromedial prefrontal cortex, posterior cingulate cortex, anterior cingulate cortex, anterior insula, and thalamus (Knutson et al, 2001;Satterthwaite et al, 2007;Kable and Glimcher, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In unipolar depression, behavioral studies have demonstrated blunted responsiveness to reward feedback (Pizzagalli et al, 2005(Pizzagalli et al, , 2008Steele et al, 2007), and neuroimaging studies have similarly found diminished reward system responses using various task paradigms (Pizzagalli et al, 2009;Smoski et al, 2009;Robinson et al, 2012;Stoy et al, 2012;Dillon et al, 2013). In contrast, several studies in non-depressed subjects with bipolar disorder have found evidence of reward system hyper-responsivity.…”
Section: Introductionmentioning
confidence: 99%
“…Altered responsiveness to reward, and to reinforcing stimuli, could therefore contribute to the generation and maintenance of depressive symptoms (Pizzagalli et al, 2009). Diminished responsiveness to commonly rewarding stimuli has already been observed in both disorders, and appears to be mainly driven by the mesolimbic dopamine system including the ventral tegmental area (VTA), a central structure in the reward processing circuitry (Keller et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies examining alterations in the mesolimbic system in UD found reduced activity during reward feedback, relative to healthy controls (HCs), in the ventral striatum (VS) including the NAcc (Knutson et al, 2008;Pizzagalli et al, 2009). Studies in BD reported more heterogeneous results, probably because of a higher variation of mood states.…”
Section: Introductionmentioning
confidence: 99%
“…MDD is characterized by impaired cortico-limbic functioning, including dysfunction in (1) the cortical brain regions that mediate attention, reward-based decision making, and monitoring of emotional salience (Ressler and Mayberg, 2007;Seminowicz et al, 2004); (2) the subcortical brain regions that process affective stimuli (Kumar et al, 2008;Pizzagalli et al, 2009) and that modulate emotional memory formation and retrieval (Dillon et al, 2013); and (3) the coordinated interactions of distributed networks of limbiccortical pathways during processing of cognitive and affective information (Drevets et al, 2008;Northoff et al, 2011). Neuroimaging treatment outcome research has shown that MDD remission is associated with decreased activity in orbitofrontal and medial prefrontal cortex Kennedy et al, 2007), increased activity in hippocampus and dorsal cingulate cortex , and increased subcortical circuits involved in responses to rewards Stoy et al, 2012) and emotion regulation (Ressler and Mayberg, 2007).…”
Section: Introductionmentioning
confidence: 99%